Strategies to avoid heat injury
Exercise in hot conditions triggers a variety of compensatory mechanisms. The two most important of these are increased blood flow to the skin and sweating. Sweating is the most powerful heat dissipation mechanism, but sweat must evaporate to have any beneficial effect. The player who is drenched in sweat is probably getting very little benefit from the fluid his body is losing. If ongoing exercise in hot conditions produces more and more body heat which cannot be dissipated, internal core temperature inevitably rises. It has been shown that most athletes collapse when their internal core temperature is in the range of 101°F to 104°F.(3) In fact, those who finish a competition in very hot weather are often those who have allowed their core temperature to rise to excessive levels. As marathon medical director Dr. Joe Wilson said of the Olympics Marathon in Atlanta, "It is the ones who finish who will need our help the most."(4) .The adverse effects of repeated elevations of core temperature to high levels have long been suspected. Many elite marathon runners avoid hard training in high heat because they feel such activity is damaging.(5) It is only recently that epidemiological information has been published on this subject. In a review of hundreds of thousands of M arine Corps recruits training at Parris Island, SC, it was found that exercise-related heat casualties increased progressively as air temperature climbed, beginning at a Heat Index of about 65°F. Unexpectedly, it was demonstrated that the risk of exercise-related heat injuries, even with exercise on relatively mild days, skyrocketed if the preceding day had included exercise in very hot weather.(6) A similar pattern was found for exercise-related heat deaths.(7) There is clear evidence that the effects of heat stress are both dose-related and cumulative.